Research Progress on the Correlation Between Mitophagy and Vascular Cognitive Impairment - LIU Yan; DONG Xingang; WANG Xiaoyuan; QI Gege; REN Yiqin; ZHOU Lianpeng; LI Hui; ZHANG Suqing; LI Weifeng (Xiehe Yixue Zazhi)
Vascular cognitive impairment (VCI), caused by cerebrovascular dysfunction, severely impacts the quality of life in the elderly population, yet effective therapeutic approaches remain limited. Mitophagy, a selective mitochondrial quality-control mechanism, has emerged as a critical focus in neurological disease research. Accumulating evidence indicates that mitophagy modulates oxidative stress, neuroinflammation, and neuronal apoptosis. Key signaling pathways associated with mitophagy—including PINK1/Parkin, BNIP3/Nix, FUNDC1, PI3K/Akt/mTOR, and AMPK—have been identified as potential therapeutic targets for VCI. This review summarizes the mechanistic roles of mitophagy in VCI pathogenesis and explores emerging therapeutic strategies targeting these pathways, aiming to provide novel insights for clinical intervention and advance the development of effective treatments for VCI.